Is the Arterial Anastomosis Time a Key Predictor of Free Flap Failure in Oncological Head and Neck Reconstruction? A Prospective Cohort Study - Cristina Cárdenas Serres; Fernando Almeida Parra; Álvaro Ranz Colio; Ángela Bueno de Vicente; Patricia de Leyva Moreno; Verónica de Prado Mendoza; Jorge Nuñez Paredes; Manuel Picón Molina; Julio Acero Sanz (Journal of Clinical Medicine, 2026)
Background/Objectives: Free flap microsurgical reconstruction is the gold standard for complex oncological head and neck defects. Despite high success rates, flap failure carries significant morbidity and oncological implications. This study aimed to identify preoperative, analytical, and intraoperative predictors of free flap non-viability in a prospective series of head and neck oncological reconstructions. Methods: A prospective observational cohort study included 98 consecutive patients undergoing microsurgical free flap reconstruction at a single tertiary centre (January 2022–December 2025). Categorical variables were analysed with Fisher’s exact test and odds ratios (OR) with 95% confidence intervals (CI); continuous variables were analysed using the Mann–Whitney U test and rank-biserial correlation (r). Multivariate logistic regression was performed for variables with p < 0.20 in univariate analysis. Results: Free flap survival was 88.8% (87/98). On univariate analysis, intraoperative vasospasm (9.2% vs. 72.7%; p < 0.001) and prolonged arterial anastomosis time (median 25 vs. 45 min; p = 0.012) showed the strongest associations with flap failure. A negative O’Brien patency test (p = 0.012) and greater number of transfused red blood cell units (p = 0.033) were also significant. No preoperative variable was significantly associated with flap outcome. On multivariate analysis, vasospasm remained the sole independent predictor of viability (p = 0.014), with arterial anastomosis time showing a persistent trend (p = 0.079). Conclusions: Intraoperative vasospasm was the principal independent determinant of flap viability, while prolonged arterial anastomosis time showed a consistent univariate association and a non-significant multivariable trend. Given the small number of flap failures (n = 11), these findings, together with the proposed intraoperative time thresholds, should be regarded as preliminary and hypothesis-generating pending external validation. These findings underscore the primacy of intraoperative technical and vascular factors and may guide surgical training and perioperative management protocols.